TEACHING ENGLISH IN BLENDED AND ONLINE FORMAT: NEW SOLUTIONS AND PRACTICE (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the features of teaching English in blended and online learning environments. The purpose of the research is to theoretically substantiate and practically approve methodological solutions aimed at increasing the effectiveness of teaching English using digital educational technologies. The research used methods of analyzing scientific and pedagogical literature, pedagogical observation, experimental training, and quantitative and qualitative processing of the results. The scientific novelty of the research is to clarify the pedagogical conditions for the effective implementation of blended and online learning of English and to develop a practice-oriented model for organizing the learning process. The practical significance of the article lies in the possibility of using the presented methodological solutions in general education schools and higher educational institutions.